2020
DOI: 10.4149/bll_2020_123
|View full text |Cite
|
Sign up to set email alerts
|

The effects of melatonin and thymoquinone on doxorubicin-induced cardiotoxicity in rats

Abstract: OBJECTIVES: This study aims to investigate the protective effects of thymoquinone and melatonin on the heart against doxorubicin-induced cardiotoxicity in rats. BACKGROUND: Melatonin and thymoquinone may play an important role in cardiotoxicity. METHODS: The subjects were divided into four groups: Control (physiological serum on 5th day), Doxorubicin (DXR), Doxorubicin+Melatonin (DXR+MEL, 10 mg/kg melatonin, intraperitoneally), and Doxorubicin+Thymoquinone (DXR+TQ, 50 mg/kg thymoquinone, orally). On the 5th da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Doxorubicin is an anthracycline group used to a variety cancers, including hematologic cancer, solid tumors, and soft tissue sarcomas, and can commonly cause heart failure and heart damage as a side effect (Pehlivan et al 2020). Doxorubicin causes serious morphological and functional cardiac changes and ultimately irreversible cardiomyopathy and heart failure (Gandhi et al 2013, Kim et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Doxorubicin is an anthracycline group used to a variety cancers, including hematologic cancer, solid tumors, and soft tissue sarcomas, and can commonly cause heart failure and heart damage as a side effect (Pehlivan et al 2020). Doxorubicin causes serious morphological and functional cardiac changes and ultimately irreversible cardiomyopathy and heart failure (Gandhi et al 2013, Kim et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin attenuated the increase in ROS production caused by doxorubicin [ 22 , 30 ]. Doxorubicin also increased nitric oxide (NO) levels in both rat and mouse models, however melatonin cotreatment effectively attenuated the increase in the NO level [ 34 , 35 , 36 ]. A reduced glutathione (GSH) level was also reduced in rats and mice treated with doxorubicin, melatonin therapy attenuating the reduction of GSH level [ 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Effect Of Melatonin On Oxidative Stress and Inflammatory Cyt...mentioning
confidence: 99%
“…Earlier researh demonstrated that TQ showed significant protective effects against Dox-induced cardiotoxicity in rats (8). More recently, a series of studies suggested that the inhibition of oxidative stress levels may be responsible for TQ action on the protective effects of cardiotoxicity (9,10). However, the potential mechanism of TQ on the protection of Dox-induced cardiotoxicity is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%